Poakcesyjne migracje zarobkowe. Kontekst teoretyczno-empiryczny. Wsparcie społeczne - Kozielska, Joanna (Wydawnictwo Naukowe UAM, 2014)
Analyses of the phenomenon of international migration of Poles do not address the biographical experiences of young Polish post-accession emigrants or their judgments and opinions. This publication is therefore targeted toward research on migration prospects for individuals as seen from three temporal perspectives. A quest for answers to questions concerning many aspects of migrants’ biographies has become an important topic – from the motives for economic emigration to the arguments in favour of returning to Poland and the entire spectrum of issues related to one’s functioning in the country of emigration as well as after returning to the country of origin. The importance of the emigration experience in the biographies of the respondents is another important aspect of this book. A temporal or permanent change of one’s life and work is a great challenge which generates many difficulties. These, in turn, are the reason why migrants should receive both formal and informal multifaceted support. The proposed approach should inspire the reader to reflect on the quality of migrants’ biographies as it blends with the mainstream humanist discourse on the temporal multidimensionality of the life of a human being who is condemned to a permanent search for his or her place (related to living, working and fulfilling one’s family role) in global reality that is constantly reconstructed anew. The monograph also presents a broad range of biographical experiences of young Polish migrants from three temporal perspectives.
Post-accession migration. The theoretical and empirical context. Social support
Keywords: Unia Europejska; emigracja; emigracja zarobkowa Polaków; młodzież; edukacja